Pre-Infarction Angina and Outcomes in Non-ST-Segment Elevation Myocardial Infarction: Data from the RICO Survey - Lorgis, Luc; Gudjoncik, Aurélie; Richard, Carole; Mock, Laurent; Buffet, Philippe; Brunel, Philippe; Janin-Manificat, Luc; Beer, Jean-Claude; Brunet, Damien; Touzery, Claude; Rochette, Luc; Cottin, Yves; et al. (PLoS ONE, 2012)
The presence of pre-infarction angina (PIA) has been shown to confer cardioprotection after ST-segment elevation myocardial infarction (STEMI). However, the clinical impact of PIA in non-ST-segment elevation myocardial infarction (NSTEMI) remains to be determined. From the obseRvatoire des Infarctus de Côte d'Or (RICO) survey, 1541 consecutive patients admitted in intensive care unit with a first NSTEMI were included. Patients who experienced chest pain <7 days before the episode leading to admission were defined as having PIA and were compared with patients without PIA. Incidence of in-hospital ventricular arrhythmias (VAs), heart failure and 30-day mortality were collected. Among the 1541 patients included in the study, 693 (45%) patients presented PIA. PIA was associated with a lower creatine kinase peak, as a reflection of infarct size (231(109-520) vs. 322(148-844) IU/L, p<0.001) when compared with the group without PIA. Patients with PIA developed fewer VAs, by 3 fold (1.6% vs. 4.0%, p = 0.008) and heart failure (18.0% vs. 22.4%, p = 0.040) during the hospital stay. Overall, there was a decrease in early CV events by 26% in patients with PIA (19.2% vs. 25.9%, p = 0.002). By multivariate analysis, PIA remained independently associated with less VAs. From this large contemporary prospective study, our work showed that PIA is very frequent in patients admitted for a first NSTEMI, and is associated with a better prognosis, including reduced infarct size and in hospital VAs. Accordingly, protecting the myocardium by ischemic or pharmacological conditioning not only in STEMI, but in all type of MI merits further attention.